The anatomy and structural connectivity of the abdominal sucker in the tadpoles of Huia cavitympanum, with comparisons to Meristogenys jerboa (Lissamphibia: Anura: Ranidae) - Gan, Li Lin; Hertwig, S.T.; Indraneil, Das; Haas, A. (Blackwell Verlag GmbH, 2016)
The tadpoles of many anuran amphibians inhabit lotic habitats and evolved oral devices to adhere to the substratum. Although published anatomical descriptions of rheophilous tadpoles exist, little is known about the modifications in gastromyzophorous tadpoles that possess abdominal suckers and live in torrential sections of streams. We describe the gastromyzophorous tadpoles of Huia cavitympanum and Meristogenys jerboa from torrential streams of Borneo, with special attention to the anatomy of their abdominal suckers and their relations to cranial structures and musculature. One cranium of H. cavitympanum and its associated muscles were computer-reconstructed in three dimensions from serial histological sections. The abdominal sucker and oral sucker comprise a set of muscles and ligaments that attach to internal skeletal structures. Some muscles could be identified to attach directly to soft tissue of the abdominal sucker and most likely contribute to suction. Comparing tadpoles of H. cavitympanum to the closely related gastromyzophorous M. jerboa reveals differences in external and internal features, such as cornu trabeculae fusion and jaw details. Because of phylogenetic uncertainties, it is unclear whether or not this structural complex evolved once or several times convergently in ranids.